Bioprinted thrombosis-on-a-chip. Issue 21 (26th September 2016) - Zhang, Yu Shrike; Davoudi, Farideh; Walch, Philipp; Manbachi, Amir; Luo, Xuan; Dell'Erba, Valeria; Miri, Amir K.; Albadawi, Hassan; Arneri, Andrea; Li, Xiaoyun; Wang, Xiaoying; Dokmeci, Mehmet Remzi; et al.
Abstract : A novel bioprinted model of thrombosis was developed to study thrombosis and thrombolysis in vitro . Abstract : Pathologic thrombosis kills more people than cancer and trauma combined; it is associated with significant disability and morbidity, and represents a major healthcare burden. Despite advancements in medical therapies and imaging, there is often incomplete resolution of the thrombus. The residual thrombus can undergo fibrotic changes over time through infiltration of fibroblasts from the surrounding tissues and eventually transform into a permanent clot often associated with post-thrombotic syndrome. In order to understand the importance of cellular interactions and the impact of potential therapeutics to treat thrombosis, an in vitro platform using human cells and blood components would be beneficial. Towards achieving this aim, there have been studies utilizing the capabilities of microdevices to study the hemodynamics associated with thrombosis. In this work, we further exploited the utilization of 3D bioprinting technology, for the construction of a highly biomimetic thrombosis-on-a-chip model. The model consisted of microchannels coated with a layer of confluent human endothelium embedded in a gelatin methacryloyl (GelMA) hydrogel, where human whole blood was infused and induced to form thrombi. Continuous perfusion with tissue plasmin activator led to dissolution of non-fibrotic clots, revealing clinical relevance of the model. Further encapsulating fibroblasts in the GelMA matrix demonstrated the potential migration of these cells into the clot and subsequent deposition of collagen type I over time, facilitating fibrosis remodeling that resembled the in vivo scenario. Our study suggests that in vitro 3D bioprinted blood coagulation models can be used to study the pathology of fibrosis, and particularly, in thrombosis. This versatile platform may be conveniently extended to other vascularized fibrotic disease models.